Analisis Perbandingan Keterampilan Kolaborasi Matematika Antar Fakultas Di Universitas Riau - Findi Rinta Fiani; Putri Handayani; Risda Ramada Fitri; Wulandari; Jesi Alexander Alim (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This study aims to analyze the comparison of mathematical collaboration skills among faculties at Universitas Riau using the Rasch Model approach. This descriptive quantitative research employed purposive sampling and involved 60 students from various faculties. The instrument used was a questionnaire consisting of 15 statements measured on a 5-point Likert scale. The analysis results showed that most items were categorized as having moderate difficulty, except for item 2, which was identified as the most difficult and misfit with the model. This is due to its sensitive content, such as the tendency to select specific group members in collaborative tasks. The Wright Map revealed a relatively balanced distribution of student abilities, with most falling into the moderate to high categories. Faculty A obtained the highest average collaboration score, followed by Faculties C, D, and B. These findings indicate that differences in teaching approaches across faculties influence students' collaborative abilities. The study recommends revising misfit items and strengthening collaborative learning strategies, especially in faculties with lower scores.